Response of the mid-latitude atmosphere to sporadic cosmic ray variations in the western Siberian region - Yanchukovsky V. L. (Solar-Terrestrial Physics)
We have analyzed spatial and temporal variations in ionospheric parameters over high and middle latitudes of Eurasia, using data from chains of high- and mid-latitude ionosondes during a severe magnetic storm in March 2015. To analyze the ionospheric response to the severe geomagnetic disturbance of solar cycle 24, we have employed ionosonde data on hourly average values of the critical frequency foF2 of the ionospheric F2 layer, the critical frequency of the sporadic layer foEs, and the minimum reflection frequency fmin. There are strong latitudinal and longitudinal differences between the features of temporal variations in the analyzed ionospheric parameters both under quiet conditions before the magnetic storm onset and during the storm. We discuss possible causes of the observed spatial variations in ionospheric parameters. The source of spatio-temporal variations in ionospheric ionization parameters may be inhomogeneities generated in the high-latitude ionosphere under conditions of increased helio-geomagnetic activity. During the magnetic storm main and recovery phases, periods of blackouts of radio signals from ionosondes were observed at both high and middle latitudes. During these periods, there was a significant increase in the absorption of radio waves used in ionosonde sounding, as well as in the frequency of occurrence of screening sporadic Es layers. The long-term effect of the negative ionospheric storm over high and middle latitudes of Europe is explained by the movement of the vast region of the reduced density ratio [O]/[N2] at thermosphere heights from the Far East and Siberia westward to Europe during the late recovery phase of the magnetic storm. Increased ionization of the ionospheric F2 layer with foF2 exceeding the level for quiet days before the onset of the magnetic disturbance over the vast region of Eastern, Western Siberia and Eastern Europe after the end of the magnetic storm in March 2015 is a manifestation of the aftereffect of magnetic storms. The increase in ionization was especially pronounced, as measured by the chain of mid-latitude ionosondes.